2020
DOI: 10.1016/j.heliyon.2020.e03921
|View full text |Cite
|
Sign up to set email alerts
|

Devil's claw (Harpagophytum procumbens) ameliorates the neurobehavioral changes and neurotoxicity in female rats exposed to arsenic

Abstract: Over 200 million people are exposed to arsenic worldwide in their daily lives. Arsenic is a toxic ubiquitous metalloid distributed in the ground water. From the last few decades it is obtaining considerable attention for its severe neurotoxic properties. In this study the neuroprotective efficacy of devil's claw (DCW), a potent antioxidant has been investigated against arsenic induced neurotoxicity in female rats. Neurotoxicity was established by oral administration of 13 mg/kg sodium arsenite. The animals wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…Each compound under investigation was tested for cell toxicity at concentrations corresponding to those potentially achievable in vivo (10–500 µg/mL: E [ 18 ], B [ 19 ], C [ 20 ], HP [ 21 ], and BS [ 22 ]. ), individually and in combination both in the presence or in the absence of TNF-α.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each compound under investigation was tested for cell toxicity at concentrations corresponding to those potentially achievable in vivo (10–500 µg/mL: E [ 18 ], B [ 19 ], C [ 20 ], HP [ 21 ], and BS [ 22 ]. ), individually and in combination both in the presence or in the absence of TNF-α.…”
Section: Resultsmentioning
confidence: 99%
“…Because chemical interactions can expose patients to potential toxic risk if combinations of multiple constituents are not accurately and precisely evaluated, we first assessed the toxicity profile of each constituent alone and in combination by measuring total cell protein content and MTT activity. For monocytes, we found that at concentrations comparable to physiologically achievable plasma concentrations, there was no toxicity for E [ 18 ], B [ 19 ], C [ 20 ], HP [ 21 ], and BS [ 22 ]. However, because endothelial cells exhibited higher sensitivity, the bioactives were tested in combination at half the concentrations of each component.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant profile of HPE was mainly studied in vivo and correlated to neurodegenerative diseases, although oxidative stress is largely involved in all inflammatory pathologies, including OA. Peruru et al analyzed GSH, SOD, and CAT levels in arsenic-induced oxidative stress rat models [ 78 ]. Doses of 200 and 400 mg/kg, p.o of HPE resulted able to restore basal levels of erythrocyte antioxidant enzymes.…”
Section: Osteoarthritis and Antioxidant Treatmentmentioning
confidence: 99%
“…On the other hand, MDA and NO content was also alleviated compared to the arsenic control group supporting the antioxidant properties of HPE. Its effect on antioxidant profile resulted to be dose-dependent [ 78 ]. These results supported data previously obtained by Bhattacharya and Bhattacharya in 1998.…”
Section: Osteoarthritis and Antioxidant Treatmentmentioning
confidence: 99%
“…depression (Coryell et al, 2019;Sodhi et al, 2019). The maximum limit set by the World Health Organization (WHO) and environmental protection agency (EPA) for arsenic in drinking water is 10 ppb, but levels up to 50 ppb are acceptable in some Asian countries like Bangladesh (Alam et al, 2018;Peruru et al, 2020;Singh et al, 2020).…”
mentioning
confidence: 99%